1978
DOI: 10.1111/j.1365-2621.1978.tb07433.x
|View full text |Cite
|
Sign up to set email alerts
|

RECOVERY OF THERMALLY INJURED Saccharomyces cerevisiae: EFFECTS OF MEDIA AND STORAGE CONDITIONS

Abstract: Resting cells of Saccharomyces cerevisiae Y2.5 were heated at 56°C for O-5 mm. Viability and thermal injury were evaluated using various media. Delayed plating after storage in water at 22°C resulted in increased counts primarily due to repair of thermal injury. Repair of injured cells was prevented by storage at 4°C or in the presence of 2,4-dinitrophenol, but was not affected by storage in the presence of actinomycin D, chloramphenicol, cycloheximide or hydroxyurea. Recovery of injured cells was inversely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…although it was originally intended that the use of such media should be for the isolation and growth characterisation of microbes. Despite the repeated and often vehement criticism which has appeared in the literature [15][16][17][18][19], agar colony counts continue to be used extensively for the enumeration of microbes for estimation of survival [20][21][22][23], in stress studies [24][25][26], and perhaps most surprisingly in public health [27][28][29][30], even though alternative accurate techniques are available [31].…”
Section: ('Ell Cultitation Methodsmentioning
confidence: 99%
“…although it was originally intended that the use of such media should be for the isolation and growth characterisation of microbes. Despite the repeated and often vehement criticism which has appeared in the literature [15][16][17][18][19], agar colony counts continue to be used extensively for the enumeration of microbes for estimation of survival [20][21][22][23], in stress studies [24][25][26], and perhaps most surprisingly in public health [27][28][29][30], even though alternative accurate techniques are available [31].…”
Section: ('Ell Cultitation Methodsmentioning
confidence: 99%
“…The reduced incidence of the ascosporogenous D. hansenii contrasts with the findings of Put and De Jong (1980) who concluded that the heat resistance of ascospores was the reason for such yeasts being common contaminants of heat-treated beverages. The absence of D. hansenii ascospores at the time of heat treatment (Put et al, 1977) and also environmental conditions such as solute content, aw and particularly pH (Graumlich and Stevenson, 1978;Juven et al, 1978) may be responsible for the observed reduced recovery of this species as a consequence of heat treatment. Generally it would appear that the yeast flora of meat and meat products is only marginally affected by ingredients and processing systems.…”
Section: Discussionmentioning
confidence: 94%
“…The plates were incubated at 25°C until maximal colony counts were obtained, usually from 5 to 10 days. Thermal injury (Graumlich and Stevenson, 1978) is thought to be responsible for the delay in colony formation. The various heating trials were replicated three to five times, usually on different days.…”
Section: Heat Resistancementioning
confidence: 99%